DEVELOPMENT OF LEARNING MEDIA BASED ON ZARKASI APPLICATION (ZAKIR CONSULTING) ABOUT MENSTRUATION AND ISTIHADHAH - Muhammad Zakir Hasibuan; Mardianto; Salminawati (SOSIOEDUKASI, 2026)
This study aimed to develop and evaluate the feasibility, practicality, and effectiveness of the Zarkasi (Zakir Consultation) application as a digital learning medium for teaching menstruation (haid) and irregular bleeding (istihadhah) in Islamic Religious Education. The research employed a Research and Development (R&D) approach using the ADDIE model, consisting of Analysis, Design, Development, Implementation, and Evaluation stages. The study was conducted at UPT SMP Negeri 27 Medan during the 2025/2026 academic year. Data were collected through interviews, observations, documentation, questionnaires, and pretest-posttest assessments. The developed application includes learning materials, consultation services, interactive quizzes, and evaluation features designed to support students’ understanding of fiqh concepts related to menstruation and istihadhah. The validation results indicated that the application was highly feasible, with material expert validation reaching 89.52% and media expert validation reaching 93.30%. Teacher and student assessments also showed very high practicality scores of 93.89% and 93.78%, respectively. The effectiveness test revealed a significant improvement in learning outcomes, with the average score increasing from 59.04 in the pretest to 87.96 in the posttest. Furthermore, the N-Gain score of 0.711 (71.1%) was categorized as high, indicating that the application effectively enhanced students’ understanding. Therefore, the Zarkasi application is considered a valid, practical, and effective learning medium for supporting Islamic Religious Education on menstruation and istihadhah.